Developed hydrogen liquefaction process using liquefied natural gas cold energy: Design, energy optimization, and techno‐economic feasibility. (14th April 2021) - Cho, Seungsik; Park, Jinwoo; Noh, Wonjun; Lee, Inkyu; Moon, Il
Summary: This study focuses primarily on improving large‐scale hydrogen liquefaction process by integrating liquefied natural gas (LNG) stream to utilize LNG cold energy. For the hydrogen liquefaction process, a large amount of energy is required for the compression and the cryogenic refrigeration system. LNG is one of the main sources for producing hydrogen, and it can be an opportunity to save energy because LNG cold energy is normally discarded into seawater during regasification. The objective of this study is to reduce the specific energy consumption and specific liquefaction cost. The proposed design which produces 300 ton/day of liquid hydrogen is compared with a base case design comprising two‐stage mixed refrigerant refrigeration cycles. To minimize the specific energy consumption, multiparameter optimization is conducted by connecting simulation results to a genetic algorithm. Through the optimization, the flow rates of LNG and MR in the precooling cycle decrease by 1.08 and 21.00 kg/s, respectively. The specific energy consumption is reduced from 4.36 to 4.07 kWh/kg‐LH2 . Particularly, in the precooling cycle where the LNG stream is integrated, it decreases by more than 26.40%. Regarding the specific liquefaction cost of hydrogen liquefaction, the capital expenses are reduced by 15.16%, and annual operating expenses are diminished by 9.05%. Therefore, the total specific cost liquefaction shows a reduction of approximately 7.7%. Overall, an efficient hydrogen liquefaction process will provide a guideline for LNG‐dependent countries by reducing the specific energy consumption and the specific liquefaction cost by recovering the waste cold energy. Abstract : LNG cold energy was effectively used for the hydrogen liquefaction process. A multi‐parameter optimization was conducted and reduced specific energy consumption from 4.36 kWh/kg‐LH2 to 4.07 kWh/kg‐LH2 . Specific liquefaction cost was decreased by 7.7%, which is one of the lowest.